Hazardous area classification for wheat flour processing plant / Mohd Aizad Ahmad, Muhammad Naqib Saifullah Noor Azman and Zulkifli Abdul Rashid - Ahmad, Mohd Aizad; Noor Azman, Muhammad Naqib Saifullah; Abdul Rashid, Zulkifli (Universiti Teknologi MARA, 2021)
Dust explosion possibly occurs in common unit operations such as mills, grinders, dryers, and other modes of transport. The basic element for the setting of hazardous zone types consist of identifies release sources, determination of classification region of hazardous area, overviewing the basic operation in wheat flour processing plant with their specification requirement and use of a suitable code or calculations to determine area scope. Therefore, this analysis can be more elaborate by classifying the hazardous area into several areas using the International Electro Technical Commission System for Certification to Standards Relating to Equipment for Use in Explosive Atmospheres standard. Thus, wheat flour processing plant area classification can be categorized according to three zones based on the quantity of an explosion into atmosphere and its release frequencies which are zones 20, zones 21, and zones 22. From the results, it can be summarized that zone 20 is almost inside or closer one with the main equipment located near the ignition source which could lead to dust explosion, whereas zone 21 and zone 22 comes after zone 20 which is a less hazardous area as compared to zone 20 areas.